Izbiranje najprimernejših mest za intramuskularno injekcijo - Šmitek, Jana (Obzornik zdravstvene nege, 2006)
With administration medications by intramuscular route it is necessary to be with the areas, single sites and appropriate muscles for injecting drugs. A muscle or site selection depends on the patient''s characteristics and the amount and sort of medication. When choosing most appropriate site for intramuscular injection we orient ourselves towards anatomical landmarks and bone prominences. The author describes five sites appropriate for injecting drugs in underlying muscles: brachial or deltoid site, two femoral sites and two gluteal sites - ventrogluteal and dorsogluteal. Most appropriate injectionsites selection for certain muscles and anatomical landmarks are described in details. Author develops and describes a new approach in selecting the most appropriate sites on gluteal area by following christa iliaca.
Keywords: injekcije; injiciranje; intramuskularne injekcije; therapy; zdravljenje